2007
DOI: 10.1007/s11211-007-0047-7
|View full text |Cite
|
Sign up to set email alerts
|

Social Class is Dead. Long Live Social Class! Stereotype Threat among Low Socioeconomic Status Individuals

Abstract: Stereotype threat effects occur when members of a stigmatized group perform poorly on a task because they fear confirming a negative stereotype that is associated with their ingroup. The present study investigates whether the observed achievement gap in standardized testing between high-and low-socioeconomic status (SES) American students can be due, in part, to this phenomenon. Participants were placed in one of four conditions that varied in level of ''threat'' related to socioeconomic status. Results show t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
133
0
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(151 citation statements)
references
References 50 publications
(51 reference statements)
9
133
0
2
Order By: Relevance
“…In particular, Croizet and Claire (1998) found performance decrements among lower SES French students under a situation of identity threat. More recently, this effect was demonstrated in a sample of college students in the United States (Spencer & Castano, 2007).In addition to this work on academic performance, SES has been found to influence social and emotional well-being in the context of higher education (Ostrove & Long, 2007). For instance, in a retrospective study, Ostrove (2003) found that women from lower and middle-class backgrounds reported feeling more alienated or belonging less during their time spent at an elite college-echoing Walton and Cohen's (2007) work on the effects of racial underrepresentation at elite private universities.…”
mentioning
confidence: 88%
“…In particular, Croizet and Claire (1998) found performance decrements among lower SES French students under a situation of identity threat. More recently, this effect was demonstrated in a sample of college students in the United States (Spencer & Castano, 2007).In addition to this work on academic performance, SES has been found to influence social and emotional well-being in the context of higher education (Ostrove & Long, 2007). For instance, in a retrospective study, Ostrove (2003) found that women from lower and middle-class backgrounds reported feeling more alienated or belonging less during their time spent at an elite college-echoing Walton and Cohen's (2007) work on the effects of racial underrepresentation at elite private universities.…”
mentioning
confidence: 88%
“…However, to our knowledge, only three studies (Croizet & Claire, 1998;Harrison, Stevens, Monty, & Coakley, 2006;Spencer & Castano, 2007) focused on the reputations of intellectual inferiority which targets individuals of low SES, and none of them were done on children. This relative disinterest on the part of researchers is even more surprising since the existence of stereotypes regarding the intellectual inferiority of individuals from disadvantaged social classes has been well demonstrated (e.g., Berjot & Drozda-Senkowska, 2007, exp.…”
Section: Scholastic Success Socio-economic Origin and Stereotype Threatmentioning
confidence: 99%
“…and those from low socioeconomic backgrounds (Spencer and Castano, 2007) in that it is normed and developed on English-speaking white middle-class subjects, whose set of educational experiences generally differ from the experiences of peoples of color and the immigrant population. Despite the Educational Testing Service's (ETS) acknowledgment of the bias, particularly against nonnative English speakers (Pitcher & Harvey, 1963, quoted in Basturk, 1999, the GRE is widely used as a criterion for admission.…”
mentioning
confidence: 99%